Implementasi Pendidikan Moral demi Menciptakan Generasi Emas 2045 - Izzati, Nazala Wahda; Sumiyati, Siti (ALSYS, 2023)
Moral education is the development or learning of character or morals in students. In this paper we describe character education innovations that have the aim of shaping the character of the golden generation of the next era. The golden generation cannot be equated with the generation of the 90s, the implementation of moral education is also almost similar to. As is known, technological advances make a big difference between the generation of the '90s and today, of course this also has an impact on the way of thinking and the way of learning in themselves. When viewed broadly about the problems that exist in Indonesia is due to a lack of self-sensitivity or morality. The problem of morals and morality is also one of the importance of moral education. In order to welcome the 2045 generation with character, moral education provides several scopes such as the scope of life coaching, morality coaching, environmental coaching and also spiritual coaching.